Color‐Tunable 3D InGaN/GaN Multi‐Quantum‐Well Light‐Emitting‐Diode Based on Microfacet Emission and Programmable Driving Power Supply. Issue 1 (9th November 2020) - Wang, Lai; Wang, Xun; Bertram, Frank; Sheng, Bowen; Hao, Zhibiao; Luo, Yi; Sun, Changzheng; Xiong, Bing; Han, Yanjun; Wang, Jian; Li, Hongtao; Schmidt, Gordon; et al.
Abstract: Color‐tunable InGaN/GaN multi‐quantum‐well (MQW) light‐emitting diodes (LEDs) are reported based on GaN microfacet structure directly grown on c ‐plane patterned sapphire substrate by metal organic vapor phase epitaxy (MOVPE) through promoting 3D growth. By adjusting GaN growth temperature and pattern arrangement, a GaN microfacet with almost pure 10 1 ¯ 1 semipolar facets is obtained. The multifacetted InGaN/GaN MQW LED chip evolves three distinct emission peaks around 630, 530, and 450 nm in electroluminescence (EL) as injection current increases from 1 to 100 mA. The EL behavior originates from locally different facets of the complex 3D structure: MQWs grown on c ‐planes and semipolar facets, respectively, which is confirmed by cathodoluminescence characterization in a scanning transmission electron microscope (STEM‐CL). Considering the dependence of emission wavelength and intensity on injection currents, a programmable power supply is designed to drive the LED. The specific color of the LED is tuned by time‐shared driving of the currents based on three channels with controllable magnitudes and duty cycle from the power supply, covering red, yellow, green, cyan, blue, and purple. Furthermore, white LEDs with high color rendering index (CRI) up to 96.1 and correlated color temperature (CCT) between 4000 and 10 000 K are achieved. Abstract : A novel and industry compatible method to realize color‐tunable InGaN/GaN multi‐quantum‐well (MQW) light‐emitting diodes (LEDs) is reported. LEDs based on 3D GaN microfacets are directly grown on c ‐plane pattern sapphire substrates (PSSs) by metal organic vapor phase epitaxy (MOVPE) and show current‐dependent color emissions. Color‐tunable LEDs are demonstrated under stimulation by a programmable driving power supply.